2017
DOI: 10.1097/jom.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Organizational Smoking Policies and Employee Vaping Behavior

Abstract: Organizations should not consider smoking and vaping to be the same when setting policy. Employers should ensure that organizational vaping policies are present and clear to all employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A recent study found that e-cigarette health risk education efforts through advertising, media coverage and interpersonal discussion can enhance perceived harmfulness of secondhand aerosol exposure [33]. Evidence also suggests that employees often report an inadequate understanding of their workplace vaping policies [34]. Educational programs at workplaces, as such, can enhance adherence to vaping regulations among employees.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that e-cigarette health risk education efforts through advertising, media coverage and interpersonal discussion can enhance perceived harmfulness of secondhand aerosol exposure [33]. Evidence also suggests that employees often report an inadequate understanding of their workplace vaping policies [34]. Educational programs at workplaces, as such, can enhance adherence to vaping regulations among employees.…”
Section: Discussionmentioning
confidence: 99%